Role of Nanomedicine in Management and Prevention of COVID-19 - Wankar, Jitendra N.; Chaturvedi, Vivek K.; Bohara, Chandrashekhar; Singh, Mohan P.; Bohara, Raghvendra A. (Frontiers in Nanotechnology, 2020)
COVID-19, coronavirus disease 2019, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a pandemic. At the time of writing this (July 28, 2020), more than 17 million people have become affected and 0.7 million people have died across the world. Remdesivir has shown the glimpses to fight the virus but yet far away from victory. Nanotechnology has proven its role in medicine to deliver the drug at the target site with the minimal side effect particularly in the anticancer domain. Most specifically, a range of nanotechnology-based products, such as nano silver, are currently on the market because they have demonstrated the potential to combat viruses. This article provides an overview of the role of nanomedicine, including soft and hard materials, and its future capabilities in the management of the disease outbreak. Taking all this into account, an attempt has been made to educate readers in the simplest way of the role of nanomedicine, which can play a pivotal role in the management of diseases.